PENGARUH STATUS SOSIAL EKONOMI ORANG TUA TERHADAP PRESTASI BELAJAR SISWA (Studi Kasus Siswa Kelas VIII SMP Negeri 1 Jember Tahun Ajaran 2016/2017) - Lilis Nur Chotimah; Hety Mustika Ani; Joko Widodo (Economic Education, University of Jember, 2017)
This study was conducted to determine the significant the of economic social status of parents to student achievement(Case Study On The VIII / Eight Grade Students Of SMP 1 Jember In 2016/2017 Academic Years). The method to determine the location of the research using purposive area that is at SMP 1 Jember. Determination the number of respondents in this study using simple random sampling method is 81 respondents. Methods of collection data used consisted of methods: questionnaires, interviews, observations, and documentation. Analysis of the data used is descriptive analysis and inferential analysis/statistics by using simple regression line analysis, analysis variance of the regression line, the F test, the effectiveness of the regression line, and Standard Error Of Estimate. The results showed that there was a significant effect of variables economic social status of parents to student achievement(Case Study On The VIII / Eight Grade Students Of SMP 1 Jember In 2016/2017 Academic Years)., which can be seen from the magnitude of F = 268,491> Ftable 3,112 = with a significance level of F = 0,000 < 0,05. The amount of the percentage of economic social status of parents to student achievement by 77.3%, while the remaining 22.7% influenced by other variables not examined in this study, such an interest, ingenuity, talent,intelligence , and others.